2018
DOI: 10.3390/molecules23092204
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for On-Gel Detection of Myrosinase Activity

Abstract: Myrosinase is an enzyme present in many functional foods and spices, particularly in Cruciferous vegetables. It hydrolyses glucosinolates which thereafter rearrange into bioactive volatile constituents (isothiocyanates, nitriles). We aimed to develop a simple reversible method for on-gel detection of myrosinase. Reagent composition and application parameters for native PAGE and SDS-PAGE gels were optimized. The proposed method was successfully applied to detect myrosinase (or sulfatase) on-gel: the detection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…As Figure A,B and Figure S11 show, when Sin was present at a concentration of 0.75 mM, Myr was detectable in the range of 0–345 mU/mL, and its linear detection range in the absorption spectrum was 0 to 172.5 mU/mL with an LOD of 2.96 mU/mL. Comparatively, our method shows superiority in sensitivity with an LOD lower than that of previously reported work. , Additionally, the linear relationship between temperature and the logarithm of Myr concentration was also exhibited by the orange line in Figure B with a similar trend as indicated previously . These results further validate that the method could be employed to Myr analysis in real samples by both temperature and absorbance variations.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…As Figure A,B and Figure S11 show, when Sin was present at a concentration of 0.75 mM, Myr was detectable in the range of 0–345 mU/mL, and its linear detection range in the absorption spectrum was 0 to 172.5 mU/mL with an LOD of 2.96 mU/mL. Comparatively, our method shows superiority in sensitivity with an LOD lower than that of previously reported work. , Additionally, the linear relationship between temperature and the logarithm of Myr concentration was also exhibited by the orange line in Figure B with a similar trend as indicated previously . These results further validate that the method could be employed to Myr analysis in real samples by both temperature and absorbance variations.…”
Section: Resultssupporting
confidence: 61%
“…However, the deficiency in specificity and the requirement of sophisticated instrumentation are always the challenging concerns. Some new methods such as immunological methods could detect denatured Myr with no nutritional value and may lead to false-positive signals, , and on-gel detection requires extensive gel preparations, which are time-consuming, labor-intensive, and not suitable for onsite Myr tests. , Consequently, it is highly desired to develop a reliable, simple, interference-free, and rapid method for real-time Myr profiles in complex dietary samples.…”
Section: Introductionmentioning
confidence: 99%
“…Toluidine blue has been used to stain leaf epidermal peels, stem epidermis, leaves, roots, myrosinase-containing myrosin cells (myrosin grains) [ 7 , 11 , 36 , 37 , 38 , 39 ], and to detect myrosinase [ 40 , 41 ]. In earlier studies, we showed that myrosin cells from semi-thin sections of transgenic B. napus seeds lacking myrosinase appeared empty or as empty holes after staining with toluidine blue [ 37 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the plant tissues are damaged (e.g., by crushing), the myrosinase comes in contact with the GLSs, resulting in the release of bioactive ITCs, nitriles, thiocyanates, epithionitriles, or oxazolidines, depending on the reaction conditions, the substrate, and the presence/absence of specifier proteins [1,2,3,14]. ITCs are the main products of this reaction at a pH range of 5–8 and at 20–45 °C [3,15].…”
Section: Introductionmentioning
confidence: 99%